Transitioning to green economic growth in China: green finance and the mediator of industrial structure upgrading - Deng, Wei; Kharuddin, Saira; Mohd Ashhari, Zariyawati; Dapo Olohunlana, Somod (Human Resources Management Academic Research Society (HRMARS), 2024)
Green finance is expected to decrease environmental pollution and the depletion of fossil energy, ultimately contributing to green economic growth (GEG). The panel data from 31 Chinese provinces between 2010 and 2020 is used to investigate the role of green finance on GEG and the mediating effect of industrial structure upgrading (ISU). This study newly creates the GEG index with 17 indicators based on the entropy-weighted TOPSIS method and performs empirical analysis using fixed effect and panel quantile regression models. The twostage least squares (2SLS) and system generalized method of moments (GMM) are also adopted to conduct the endogeneity test. It is found that the information presented by the GEG index accurately reflects the state of affairs in China's provinces, indicating that this index is valid. Green finance enhances GEG, and this boost increases as the level of GEG rises. The findings also imply that ISU positively mediates the impact of green finance on GEG, accounting for 28.4% of the total impact. The COVID-19 pandemic overall shows a promotion of GEG, although it hampers economic growth.